Municipal solid waste collection systems An indicator to assess the reusability of products - Degli Esposti, Anna (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2021)
GRAPHICAL ABSTRACT: [Formula: see text]